Comparison of Hydrodynamic Models for the Electromagnetic Nonlocal Response of Nanoparticles. Issue 12 (9th September 2018) - Kupresak, Mario; Zheng, Xuezhi; Vandenbosch, Guy A. E.; Moshchalkov, Victor V.
Abstract: Since deep nanoscale systems are increasingly studied, accurate macroscopic theories dealing with quantum mechanical effects are in high demand. Concerning the electromagnetic response of nanoplasmonic systems, several hydrodynamic models have been proposed, each introducing an additional boundary condition (ABC) to describe the behavior of the plasmonic electron cloud. Four hydrodynamic approaches with four different boundary conditions are compared: the hard wall hydrodynamic model with the Sauter ABC, the curl‐free hydrodynamic model with the Pekar ABC, the shear forces hydrodynamic model with the specular reflection ABC, and the quantum hydrodynamic model with the corresponding ABC. This is done by investigating near‐ and far‐field features of a metallic nanosphere. It is shown that different hydrodynamic models may result in an entirely different prediction of the nanoparticle's response. These models are validated by using other local and nonlocal response models and experimental results. Abstract : In this work, a detailed comparative study between different nonlocal hydrodynamic models with additional boundary conditions is performed. These models consider quantum mechanical effects, which govern the optical response of structures at deep nanometer scale. Essentially, the models are tested through an investigation of near‐ and far‐field characteristics for a metallic nanosphere.